Behavior of sulfur mustard in sand, concrete, and asphalt matrices: Evaporation, degradation, and decontamination. Issue 12 (15th October 2017) - Jung, Hyunsook; Choi, Seungki
ABSTRACT: The evaporation, degradation, and decontamination of sulfur mustard on environmental matrices including sand, concrete, and asphalt are described. A specially designed wind tunnel and thermal desorber in combination with gas chromatograph (GC) produced profiles of vapor concentration obtained from samples of the chemical agent deposited as a drop on the surfaces of the matrices. The matrices were exposed to the chemical agent at room temperature, and the degradation reactions were monitored and characterized. A vapor emission test was also performed after a decontamination process. The results showed that on sand, the drop of agent spread laterally while evaporating. On concrete, the drop of the agent was absorbed immediately into the matrix while spreading and evaporating. However, the asphalt surface conserved the agent and slowly released parts of the agent over an extended period of time. The degradation reactions of the agent followed pseudo first order behavior on the matrices. Trace amounts of the residual agent present at the surface were also released as vapor after decontamination, posing a threat to the exposed individual and environment.